Effect of Ultrasonic-Assisted Thermal Treatment on the Structure and Solubility of Rapeseed Protein - ZHAO Kangyu, YANG Ping, MA Junkun, SHU Wenjing, YANG Feng, XIE Yisha, LIU Qingqing (Shipin Kexue)
The effects of ultrasound (200, 400 and 600 W)-assisted thermal treatment (25, 60 and 90 ℃) on the structure and solubility of rapeseed protein were investigated. For the individual thermal treatment groups, as the heating temperature increased, protein aggregation occurred. The particle size increased from 1 188.18 to 5 630.00 nm. The solubility decreased from 8.6% to 5.6% and the absolute value of the zeta potential decreased. This was accompanied by a conformational transition from an ordered to a disordered state. After the combined ultrasonic-thermal treatment, the spatial structure of protein molecules was unfolded, thus resulting in the breaking of peptide bonds and the exposure of hydrophobic groups. Compared with the 25 ℃ treatment, its combination with 600 W ultrasonication promoted the breakdown of protein aggregates and reduced the particle size to 1 155.27 nm, leading to the exposure of more polar groups, increased amounts of charged residues, increased surface hydrophobicity, mutual transformation of secondary structures, and a significant improvement in protein solubility (up to 57.31%). The results of this study provide a scientific basis for research on combined modifications and solubility regulation of rapeseed protein.